Mitochondrial non-coding RNA in nasopharyngeal carcinoma: Clinical diagnosis and functional analysis - Wang, Feng; Li, Xiaoyu; Li, Cong (Frontiers in Genetics, 2023)
Background: Nasopharyngeal carcinoma (NPC) is a common head and neck cancer with high incidence in Southeast Asia. Despite advances in treatment, the diagnosis of NPC remains a challenge due to its non-specific symptoms and high rate of false negatives. In this study, we aimed to identify novel non-coding RNAs (ncRNAs) as diagnostic biomarkers for NPC. Mitochondrial non-coding RNAs (mtio-ncRNAs) have been shown to play important roles in regulating various cellular processes. However, their specific functions and underlying mechanisms are largely unknown. Methods: We investigated the expression and biological function of mtio-ncRNAs in the human NPC cell line C666-1. By using high-throughput sequencing, we identified several significantly expressed mtio-ncRNAs in C666-1 cells and analyzed their target genes and enriched pathways using tsRFUN. Results: Our results showed that these significantly expressed mtio-ncRNAs mainly enriched in Cancer Gene Neighborhoods and targeted genes GCM1 and ACTG1. To validate the bioinformatics predictions, we synthesized two mtio-ncRNAs, t00846456 and t00048674, and transfected them into C666-1 cells. Our results showed that the expression of GCM1 was significantly increased by transfection of t00846456, while the expression of ACTG1 was significantly increased by transfection of t0048674. Additionally, the migration ability of the transfected cells was also enhanced Discussion: Our findings provide novel insights into the biological functions of mtio-ncRNAs and their potential applications in cancer diagnosis and treatment.